1981
DOI: 10.1177/00220345810600080801
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Development and Growth of Cranial Bones and Masticatory Muscles in Postnatal Mice

Abstract: Development and growth of cranial bones and masticatory muscles in postnatal mice, assessed by roentgenographic cephalometry and histochemistry, revealed that it corresponded to the attachment of the masticatory muscles, but not necessarily to growth and development of the individual muscles. Physiological functions of the dentofacial complex correlated with development of the muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…). Indeed, here we found that the masseter as the dominant masticatory muscle in mice (Nakata, ) was significantly lighter in the mice fed on softened pellets than those fed on hard pellets. As muscle force depends on muscle mass, the soft food mice may have produced less masticatory loads, thus providing less mechanical stimuli to the bone (Ross et al.…”
Section: Discussionmentioning
confidence: 60%
“…). Indeed, here we found that the masseter as the dominant masticatory muscle in mice (Nakata, ) was significantly lighter in the mice fed on softened pellets than those fed on hard pellets. As muscle force depends on muscle mass, the soft food mice may have produced less masticatory loads, thus providing less mechanical stimuli to the bone (Ross et al.…”
Section: Discussionmentioning
confidence: 60%
“…As the masseter muscle is closely related to the mandibular growth, clinicians should consider the effect of BTX‐A on the mandibular growth when injecting it into masseter muscle of the growing patients. It has long been thought that bony processes are dependent on normal muscle function for their development and maintenance (Nakata, 1981; Hinton, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Herring (1985) has speculated that the earliest stages of oral motor development are "dominated by the progressive formation of neuromuscular and CNS connections", whereas later changes are represented as secondary to musculoskeletal growth. For example, the reorganization of central motor pathways has been observed to coincide with the early shift from sucking to chewing (Iriki et al 1988), whereas more gradual changes in muscle activation patterns through development have been correlated with ontogenetic changes in skull/mandibular size and geometry (Herring 1985;Lakars and Herring 1980;Nakata 1981).…”
Section: Introductionmentioning
confidence: 99%